SOCIODEMOGRAPHIC FACTOR RELATIONSHIP WITH INFANT SURVIVAL IN INDONESIA - Yasmine Nurfirdaus; Philip Etabee Macdonald Bassey (Universitas Airlangga, 2021)
Child survival can be reflected in the presence of the Infant Mortality Rate (IMR). Indonesia has an Infant Mortality Rate (IMR) according to the 2017 IDHS, which reaches 24 deaths per 1000 live births. This figure has decreased compared to a survey conducted by the 2012 IDHS, where infant mortality reached 32 deaths per 1000 live births. Even though it experienced a decrease, the IMR in Indonesia was higher when compared to the IMR in other Southeast Asian countries. Socioeconomic factors for individuals, families, and communities, including the influence of infant mortality. Not only that, but infant mortality can also be due to the absence of awareness of maternal health. Thus, this study aims to determine several variables related to survival in infants in Indonesia. This type of research is a non-reactive study. This study uses quantitative analysis and a methodical approach with a cross-sectional approach that takes data from the 2017 IDHS. This study took a sample following the 2017 IDHS with the criteria that mothers who had babies still drank breast milk, were born single, and were still alive after the first three days in Indonesia. The number of respondents in this study was 7,599 mothers with babies. Analysis of the research data using Chi-Square analysis. Bivariable analysis shows that infants' survival has a relationship with the mother's education, type of area, and welfare level. However, infant survival also has no association with the age of the mother and birth attendants. Counseling pregnant women regarding risks, causes,